Minimnya Semangat Belajar Siswa Di SMP Hidayatul Mubtadi'in - Putri Lathifa; Ageng S. Kanda Saepudin (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Causes of lack of enthusiasm for learning among Hidayatul Mubtadi'in Middle School students. Based on questionnaires and interviews conducted with Hidayatul Mubtadi'in Middle School students. Boring classroom learning is the main factor in students' low enthusiasm for studying at Hidayatul Mubtadi'in Middle School. Boring learning makes students sleepy, annoyed, and indifferent to the material being explained. Meanwhile, enthusiasm for learning greatly influences the learning process and students' future. This factor is not very good for students, therefore learning requires learning methods that are attractive to students. These factors can minimize students' enthusiasm for learning, including Hidayatul Mubtadi'in Middle School students.